Criminal Diasporas: Transnational Networks and Socio-Cultural Integration in Peshawar, Pakistan - Zakir Hussain; Murad Ali; Farman Ali; Jahan Ul Mulk; Umar Daraz; Salman Khan (Review Journal of Social Psychology & Social Works, 2024)
This study investigates the intricate dynamics of criminal diasporas and their socio-cultural integration within the context of Peshawar, Pakistan, amidst the challenges of globalization and transnational crime. Thematic analysis of semi-structured interviews has demonstrated major themes that correspond the process of socio-cultural adaptation with network structures, and community impacts of globalization. Combined contributions of law enforcement officials, community leaders, civil society representatives and individuals who have been directly or remotely involved in transnational criminal activities shed pertinent knowledge about different aspects of the phenomenon. This study shows criminal diaspora challenges can only be met effectively with an integrated action plan that includes community-based approaches, power building activities, cooperative sectoral efforts, cultural understanding measures, secured operations, preventive policies, legal structure, and international teamwork. If policymakers understand what is out there and approach current challenges by creating both resilience and social inclusion along with enhanced security, safer social structures have been developed in both Peshawar and beyond these borders.